The present study was conducted with the aim of designing and validating a multicultural high school art curriculum model with an emphasis on Iranian ecosystems - Froutan, Mostafa; Sadeghi, Alireza; Mehrmohammadi, Mahmoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Purpose: Various intellectual, political, and religious schools consider art as an efficient tool for the development of various concepts and knowledge in the society and use it in the education of teenagers in a way that suits their goals. The present study was conducted with the aim of designing and validating a multicultural high school art curriculum model with an emphasis on Iranian ecosystems. Research Method: The research method was exploratory mixed (qualitative-quantitative). In the present study, the statistical population for the qualitative section included all documents related to the research topic, of which 14 documents were selected by the systematic data method of the foundation, and in the quantitative section included art teachers of Tehran high schools in the field of art, 230 people were selected as the sample size. The sampling method at this stage was cluster random. The research tool in the qualitative section was data collection focused on research documents in the field of multicultural curriculum with emphasis on Iranian ecosystems. In a small part, a researcher-made questionnaire was used. The validity and reliability of the instruments were evaluated and confirmed. The method of data analysis in the qualitative part of the theoretical coding was taken from the method of data theory of the foundation. In the quantitative part, to answer the research questions, tests such as Pearson correlation, confirmatory factor analysis and t-test were used. Results: The results of factor analysis showed that the categories of education on how to interact between cultures, the development of cooperation and interaction skills, familiarity with cultures and communities, curriculum objectives, curriculum content, learning process, art production and art criticism are central components and formation Donors were identified. Conclusion: the country's multicultural society, attention to the needs and growth of students and respect for different cultures were identified as causal or influential categories of the curriculum. In addition, educational justice, cultivation of thinking skills, personal growth and development, familiarity with the history of culture and art and peace and peaceful coexistence were identified as consequential categories.